2019
DOI: 10.1590/0104-530x4062-19
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for defense logistics

Abstract: Defense logistics (DL) is an important and yet unexplored knowledge area of Production Engineering. Therefore, the purpose of this paper is to establish the DL problem domain. The focus is on industrial, technological, institutional, organizational and, specially, strategic management aspects applied to logistics in the defense sector. It also proposes a conceptual framework identifying DL objectives, functional areas and interfaces with the environment. The framework defines the Defense Logistics Base (DLB) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The military logistics revolution is closely related to the available technology [86]. The reason why is because, historically, the use of technology has allowed military logistics to respond to the requirements of the troops, increasing the capacity of the army and changing the state [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…The military logistics revolution is closely related to the available technology [86]. The reason why is because, historically, the use of technology has allowed military logistics to respond to the requirements of the troops, increasing the capacity of the army and changing the state [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…A literatura atualmente distingue dois tipos de logística, militar e empresarial, que se diferem sob vários aspectos, como objetivo, foco, ambiente e medidas de desempenho. Quanto ao objetivo, a logística militar, centrada nas ações de Estado, visa à prontidão operacional das Forças Armadas, enquanto que a logística empresarial visa essencialmente ao lucro (Brick 2019). Quanto ao foco, a logística militar preocupa-se com a sustentação do combate, enquanto que a logística empresarial preocupa-se com alianças estratégicas, distribuição física e serviço ao cliente.…”
Section: Teoria Da Logísticaunclassified
“…The indings of the research revealed that the Indonesian maritime security had not been developed and organized in a comprehensive and structured way as per the perspective of defence management of the other nations. Gestão and Brick (2019) had stated that the concept of DL (defence logistics) is a signi icant but not an explored area of knowledge regarding the production engineering. Hence, the aim of this study was to develop the domain of issues regarding defence logistics.…”
Section: Review Of Literaturementioning
confidence: 99%